An orthogonal and reactivity-based one-pot glycosylation strategy for both glycan and nucleoside synthesis: access to TMG-chitotriomycin, lipochitooligosaccharides and capuramycin. Issue 14 (2nd March 2021) - He, Haiqing; Xu, Lili; Sun, Roujing; Zhang, Yunqin; Huang, Yingying; Chen, Zixi; Li, Penghua; Yang, Rui; Xiao, Guozhi
Abstract : The first one-pot glycosylation strategy for both glycan and nucleoside synthesis based on glycosyl ortho -(1-phenylvinyl)benzoates has been developed, which is applied to the synthesis of TMG-chitotriomycin, lipochitooligosaccharides and capuramycin. Abstract : Both glycans ( O -glycosides) and nucleosides ( N -glycosides) play important roles in numerous biological processes. Chemical synthesis is a reliable and effective means to solve the attainability issues of these essential biomolecules. However, due to the stereo- and regiochemical issues during glycan assembly, together with problems including the poor solubility and nucleophilicity of nucleobases in nucleoside synthesis, the development of one-pot glycosylation strategies toward efficient synthesis of both glycans and nucleosides remains poor and challenging. Here, we report the first orthogonal and reactivity-based one-pot glycosylation strategy suitable for both glycan and nucleoside synthesis on the basis of glycosyl ortho -(1-phenylvinyl)benzoates. This one-pot glycosylation strategy not only inherits the advantages including no aglycon transfers, no undesired interference of departing species, and no unpleasant odors associated with the previously developed orthogonal one-pot glycosylation strategy based on glycosyl ortho -alkynylbenzoates, but also highly expands the scope (glycans and nucleosides) and increases the number of leaving groups that could be employed for the multistep one-pot synthesis (up to the formation of four different glycosidic bonds). In particular, the current one-pot glycosylation strategy is successfully applied to the total synthesis of a promising tuberculosis drug lead capuramycin and the divergent and formal synthesis of TMG-chitotriomycin with potent and specific inhibition activities toward β- N -acetylglucosaminidases and important endosymbiotic lipochitooligosaccharides including the Nod factor and the Myc factor, which represents one of the most efficient and straightforward synthetic routes toward these biologically salient molecules.